Community Engagement In Strengthening Religious Piety Through Sanad-Based Prayer Training In Tulung Village, Kedamean District - Mukhlas, Abdulloh Arif; Al-Ayubi, Sholihudin; Sa’diyah; Drajat, Habiba; Chandra, Muhammad Aditya; Hasan, Safira; Zulaihah, Rina (PUDAK: Local Wisdom Community Journal, 2024)
This assistance aims to increase the value of piety through training in prayer practices in accordance with what is taught by Islam. This community assistance is carried out in Tulung village, a community that has a less than good religious historical background. In the past, Tulung village was a PKI (Indonesian Communist Party) base area. The activities in this assistance are deepening the practice of bersanad prayer. Bersanad prayer is an in-depth study of movements and readings in obligatory and sunnah prayers. This bersanad prayer has an effort to connect prayer movements with teachers and scholars. This research was conducted by observing the people of Tulung village, Kedamean sub-district. The method used to carry out this community service is PAR (Participatory Action Research) where this assistance is very important to be a solution to problems in society. Participatory Action Research PAR is one of the research models looking for something related to the process that connects research with the process of social change.